A phase II study of docetaxel and carboplatin with concurrent radiation therapy for locally advanced head and neck cancer - Imjai Chitapanarux (2018)
Objective: In this study we evaluate the clinical response and safety profile of a regimen of docetaxel. +. carboplatin concurrent with radiotherapy (RT) in locally advanced squamous cell carcinoma of head and neck (HNSCC). Methods: Between January 2006 and December 2008, we enrolled 38 patients (stage IVA: 29 patients; stage III: 9 patients). Fourteen had oral cavity cancer (tongue 10, buccal mucosa 2, alveolar ridge 1, floor of mouth 1), 10 had oropharyngeal cancer (base of tongue 5, tonsil 5), 13 had laryngeal cancer, and 1 had maxillary sinus cancer. Patients received concurrent docetaxel 15mg/m21-h infusion plus carboplatin AUC of 2, 30-min infusion on days 1, 8, 15, 22, 29, and 36. RT began on day 1 of concurrent chemotherapy with 2cGy/fraction, 5 fractions/week (total dose: 66-70cGy). Tumor was assessed by CT scan 3 months post-completion of concurrent chemoradiotherapy. Results: Thirty-five patients were evaluated (2 refused to receive all treatments, 1 had serious adverse event [rash, wheezing] from docetaxel first dose). The primary study endpoint of clinical response was achieved in 26 (74.3%) patients, 6 (17.1%) had stable disease, and 3 (8.6%) had disease progression. The 2-year disease-free survival was 62.9% (CI: 45.85-79.95%). The 2-year overall survival was 64.1% (CI: 43.52-84.68%). The most common Grade 3 toxicities were mucositis, xerostomia and dysphagia (13.9% each) and dermatitis (11%). No Grade 4 toxicities were observed. Conclusion: In conclusion, this study with a limited number of patients, docetaxel. +. carboplatin concurrent with RT appears to show acceptable activity and is generally well tolerated in patients with locally advanced HNSCC. © 2010 Elsevier Ireland Ltd.